Design of microstrip miniature antenna for RFID applications - Obsiye, Abdi Khadar Hassan (Kulliyyah of Engineering, International Islamic University Malaysia, 2009)
Radio Frequency Identification (RFID) has drawn great attention nowadays, because of its great potential for use in many applications. Size of the RFID tags, its read range and its ability to work with metallic objects are among the main challenges to this technology. Miniaturize the size of the RFID antennas cause gain degradation, while nearby metallic objects cause detuning of the antenna. Two different types of RFID tag antennas have been proposed to overcome these challenges. A compact planar inverted–F (PIFA) antenna was designed using two parallel patches. A PIFA of 50 mm × 50mm × 8 mm has a read range of more than 5 m at the resonant frequency of 915 MHz. compact. PIFA can be attached to metallic objects without performance degradation. Recently there are new interests on applying ultra-wideband (UWB) technology in developing RFID systems. UWB has advantages over the conventional narrowband RFID. Crescent antenna of 35 mm × 30 mm × 1.6 mm was designed for UWB-RFID tags. The conductive material has a great impact on UWB-RFID. To overcome this effect a layer of foam was attached to the antenna to act as a buffer. The proposed antenna has a maximum read range of between 0.9m and 4.4m with the ability to cover the UWB with the existing of metallic objects.